Parental Involvement in Maintaining Children's Social Interactions - Juwinner Dedy Kasingku; Robert Siby (Edumaspul: Jurnal Pendidikan, 2024)
This research explores the importance of parents' roles in shaping children's social interactions, especially in facing the increasing challenges of peer pressure among teenagers. Using qualitative research methods, data was obtained through literature review and relevant online sources. The findings show that families play a crucial role in shaping children's character, habits, and actions. Additionally, children's social interactions are greatly influenced by the family environment, which serves as the foundation for their development. Good communication between parents and children, as well as the establishment of clear rules and boundaries within the family, are key to fostering positive social interactions. Parents also need to provide age-appropriate sex education to help children understand the risks of peer pressure. Thus, the role of parents in guiding children and creating a healthy family environment is very important to protect children from the negative impacts of peer pressure and to build strong character and readiness to face future challenges.